AgriWeedClim database: A repository of vegetation plot data from Central European arable habitats over 100 years. Issue 3 (8th August 2022) - Glaser, Michael; Berg, Christian; Buldrini, Fabrizio; Buholzer, Serge; Bürger, Jana; Chiarucci, Alessandro; Chytrý, Milan; Dřevojan, Pavel; Follak, Swen; Küzmič, Filip; Lososová, Zdeňka; Meyer, Stefan; et al.
Abstract: Aims: Arable habitats (i.e. fields, orchards, vineyards, and their fallows) were created by humans and have been essential elements in Central European landscapes for several millennia. In recent decades, these habitats have been drastically altered by changes in land use as well as agricultural practices and, more recently, by climate change. These changes have precipitated substantial changes in vegetation and their spatial and temporal trajectories have not yet been exhaustively studied. Here, we present the AgriWeedClim database — a new resource of vegetation plot (relevé) data of arable habitats in Central Europe. Location: Germany, Czech Republic, Slovakia, Switzerland, Liechtenstein, Austria, Hungary, Northern Italy, Slovenia, Croatia. Methods: Vegetation plot data were obtained from large repositories (e.g. European Vegetation Archive), specialized regional databases, colleagues and the literature. Data were then checked for completeness and standardized (e.g. taxonomy, nomenclature, crop types). Species were assigned native, archaeophyte (i.e. alien species introduced before c. 1492 CE) or neophyte (i.e. alien species introduced after c. 1492 CE) status. Results: The AgriWeedClim database version 1.0 contains georeferenced data from 32, 889 vegetation plots sampled from 1916 to 2019. Conclusions: We provide an overview of this new resource and present example analyses to show its content and possible applications. We outline potential research questions including analysis of patterns and causes of vegetation changes in arable habitats from the early 20th century to the present. Abstract : Due to changes in agricultural practices, land use and, more recently, climate, the vegetation of arable habitats in Central Europe has undergone large, understudied, changes. The AgriWeedClim database is a collection of 32, 889 vegetation plots compiled from large data repositories, individual contributors and digitization efforts. It offers a wide range of possible applications for biodiversity and vegetation science.